Stachytarpheta grandiflora, a new species of Verbenaceae from the Parque Nacional da Serra da Canastra, Minas Gerais, Brazil - Cardoso, Pedro Henrique; Neto, Luiz Menini; Salimena, Fátima Regina Gonçalves (Phytotaxa, 2019)
Stachytarpheta grandiflora, an endemic species to campos rupestres of the Parque Nacional da Serra da Canastra, west of Minas Gerais, Brazil, is described and illustrated. The new species is characterized by pubescent branches, leaves with acute apex, petiole 0.5–1 cm long, bracts 0.7–1 cm long, with caudate apex, calyx 1.5–1.6 cm long, pubescent, 2-toothed and corolla 2.3–3 cm long, dark blue. It belongs to the informal group “Sellowiana”. We provide a detailed diagnosis, a morphological comparison with the most similar species, a key for the informal group where the new species belongs, a distribution map, conservation status and illustrations.